2021
DOI: 10.3389/fped.2021.629549
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement on the Management of Duchenne Muscular Dystrophy in Saudi Arabia During the Coronavirus Disease 2019 Pandemic

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has caused overwhelming challenges in healthcare worldwide. During such an outbreak, some needs of high-risk groups who require regular follow-ups and long-term management are not met. The vulnerable populations include patients with Duchenne muscular dystrophy (DMD). Duchenne muscular dystrophy is characterized by respiratory complications caused by muscle weakness. Hence, patients with this condition are at high risk of severe diseases including CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…19 23 26 32 33 Eighteen articles/guidelines reported that the decision should consider individual patient’s characteristics to provide individualised care. 34 35 Details on patient’s eligibility criteria for telehealth mentioned in the articles/guidelines included in the review are provided in online supplemental file 3 .…”
Section: Resultsmentioning
confidence: 99%
“…19 23 26 32 33 Eighteen articles/guidelines reported that the decision should consider individual patient’s characteristics to provide individualised care. 34 35 Details on patient’s eligibility criteria for telehealth mentioned in the articles/guidelines included in the review are provided in online supplemental file 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Current WHO recommendations highlight the role of telemedicine [ 19 ]. In Saudi Arabia, Bamaga et al advised DMD patients to proceed with virtual clinic visits, if possible, to avoid unnecessary contact with other patients who are probably infected [ 20 ]. In our previous study, we presented the possibilities and benefits of home e-monitoring of the pulmonary function in DMD patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine and telerehabilitation demonstrate a promising alternative strategy, but this seems to be potentially compromised and unexplored to a great extent in developing countries. Many patients with neuromuscular disease rely heavily on caregiver support throughout their lifetime and thus maintaining the health of their primary caregivers is also a significant consideration in the health and well-being of the patients [23,24].…”
Section: Learned Lessons Are Emergingmentioning
confidence: 99%